Immunosuppressive profiles in liquid biopsy at diagnosis predict response to neoadjuvant chemotherapy in triple-negative breast cancer. (November 2020) - Salvador-Coloma, Carmen; Santaballa, Ana; Sanmartín, Elena; Calvo, David; García, Ana; Hervás, David; Cordón, Lourdes; Quintas, Guillermo; Ripoll, Francisco; Panadero, Joaquín; Font de Mora, Jaime
Abstract: Background: Triple-negative breast cancer (TNBC) is characterised by high pathological complete response to neoadjuvant chemotherapy (NAC). However, refractory and poor NAC responders still face very poor outcome, emphasising the urgent need for tools that facilitate identification of these patients, so that surgery or alternatives to NAC are considered early in the treatment protocol. Materials and methods: We combined metabolomics, exosome circulating miRNAs and flow cytometry experimental approaches in TNBC patients at diagnosis with immunohistochemistry in needle biopsy tumours to generate NAC-response predictive models. We also co-cultured and studied crosstalk between isolated patient-derived early myeloid-derived suppressor cells (eMDSCs) and TNBC cancer cell lines. Results: Blood-derived liquid biopsy biomarkers display a novel immunosuppressive profile of tryptophan-derived metabolites and eMDSC levels that significantly predict NAC response. Notably, indoleamine 2, 3-dioxygenase 1 (IDO1) expression in tumour cells inversely correlated with circulating tryptophan levels but directly correlated with the level of eMDSCs. In addition, a set of circulating exosome miRNAs that target pathways of immune maturation also predicted poor NAC response prior to chemotherapy. Interestingly, expression of IDO1 increased when TNBC cell lines were co-cultured with patient-derived eMDSCs and this, in turn, promoted proliferation of eMDSCs. Conclusion: Our findings demonstrate that the suppressive pathways of the immune system play a key role in modulating the NAC response in TNBC. We identify a crosstalk mechanism between tumour cells and eMDSCs that exacerbates immunosuppression. These results provide a potential new tool to identify poor NAC responders for alternative strategies of treatment, including early surgical resection of the tumour, and to explore in them alternative immune therapies. Graphical abstract: Image 1 Highlights: Circulating immunosuppressive biomarkers predict NAC response in TNBC. Tumour IDO1 expression inversely correlates with circulating eMDSC and free tryptophan. Crosstalk of eMDSCs and TNBC cells explains immunosuppressive profiles at diagnosis.